Therapeutic Effect of Hijamah (Cupping Therapy) on Lipid Profiles and Apolipoprotein in Hypercholesterolemic Patients - Pelawati, Ratna; Widada, Wahyudi; Wulandari, Endah; Mardiyanti, Mardiyanti; Samsiah, Samsiah (Jurnal Keperawatan Soedirman, 2022)
Hijamah or cupping therapy has a therapeutic effect on cholesterol. However, there is still a lack of studies that investigate the potential effect of cupping in managing apolipoprotein B as a proatherogenic agent and apolipoprotein A-1 as an anti-proatherogenic agent. This study aims to explore the effect of cupping therapy on lipid profiles and apolipoproteins in hypercholesterolemic patients. A pre-post experimental design without controls were used. Consecutive sampling was applied to 40 dyslipidemia respondents. The lipid profiles and plasma apolipoproteins A-I (ApoA-I) and apolipoproteins B (ApoB) were measured after the respondents fasted for 12 hours before cupping therapy and 24 hours after cupping therapy. The Wilcoxon sign-rank test was used for the data analysis. The following results were found: average lipid profile (mg/dL) and apolipoprotein (µg/mL) pre vs post cupping: Total Cholesterol (Pre-test vs Post-test) 328 vs 283 (P-value 0.003); TG 238 vs 204 (P- value 0.007); HDL 78.5 vs 85 (P- value 0.000); LDL 195 vs 158 (P- value 0.001); ApoA-1 0.07 vs 0.67 (P-value 0.000); ApoB 2.04 vs 1.82 (P-value 1.000); ApoB/ApoA-1 ratio 30.22 vs 2.93 (P- value 0.000); cholesterol/HDL ratio 4.06 vs 3.08 (P- value 0.332); TG/HDL ratio 3.01 vs 2.83 (P- value 0.104); LDL/ApoB ratio 90.75 vs 83.82 (P- value 0.0837). In conclusion, cupping therapy reduces total cholesterol, TG, LDL, and apoB/ApoA-1 ratio and increases HDL significantly in dyslipidemic patients. Nurses are suggested to include cupping therapy (hijamah) in their intervention for reducing hypercholesterolemia in dyslipidemic patients.